1996
DOI: 10.1093/carcin/17.11.2297
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of cDNAs representing dithiolethione-responsive genes

Abstract: Dithiolethiones inhibit tumorigenicity elicited by many structurally diverse carcinogens in numerous target tissues. These protective actions are associated with the induction of several carcinogen detoxification enzymes, some of which have only recently been discovered. In order to identify additional novel inducible detoxification response genes, a cDNA library was prepared from liver of rats treated with 1,2-dithiole-3-thione (D3T) and was screened by a differential hybridization method. Complementary DNA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 23 publications
3
58
0
Order By: Relevance
“…pCMV-3Tag-hPtGR-1 or pCMV-3Tag-1 plasmids were transfected into cells with Lipofectamine 2000 (Invitrogen) overnight. Rat-PtGR-1 overexpression was obtained by transfection with a pCAGGS-EGFP-rat-PtGR-1 plasmid in which rat-PtGR-1 cDNA-tagged with EGFP was ligated into the mammalian expression vector pCAGGS (41,42). Expression of recombinant as well as endogenous PtGR-1 was assessed by Western blot analysis using FLAG (Santa Cruz), GFP (Sigma), and PtGR-1 (Aviva Systems Biology) antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…pCMV-3Tag-hPtGR-1 or pCMV-3Tag-1 plasmids were transfected into cells with Lipofectamine 2000 (Invitrogen) overnight. Rat-PtGR-1 overexpression was obtained by transfection with a pCAGGS-EGFP-rat-PtGR-1 plasmid in which rat-PtGR-1 cDNA-tagged with EGFP was ligated into the mammalian expression vector pCAGGS (41,42). Expression of recombinant as well as endogenous PtGR-1 was assessed by Western blot analysis using FLAG (Santa Cruz), GFP (Sigma), and PtGR-1 (Aviva Systems Biology) antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…It is coregulated in the rat with a variety of phase 2/antioxidative enzymes, including NAD(P)H:quinone reductase, glutathione S-transferases, and UDP-glucuronosyltransferases, through the Keap1/Nrf2 signaling pathway (2). ␣,␤-Unsaturated aldehydes and ketones are electrophilic and capable of reacting, via a Michael addition mechanism, with important cellular nucleophiles, which in turn leads to macromolecular (protein, DNA) dysfunction and cell death.…”
Section: Nad(p)h-dependent Alkenal/one Oxidoreductase (Aor)mentioning
confidence: 99%
“…2 Whereas the former two classes of compounds are inactive metabolites, 15-deoxy-⌬ 12,14 -prostaglandin J 2 is thought to be an endogenous activator of the Nrf2 transcription factor (8). Recently, AOR was also found to reduce the 8,9-double bond of the mycotoxins illudins S and M (9).…”
Section: Nad(p)h-dependent Alkenal/one Oxidoreductase (Aor)mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies demonstrated that oltipraz and many related dithiolethiones were potent inducers of enzymes concerned with the maintenance of reduced glutathione pools as well as enzymes important to the detoxication of electrophiles and free radicals. Genes now recognized to be induced by dithiolethiones in vivo include alpha, mu and pi isoforms of GSTs, UDP-glucuronosyl transferases, NAD(P)H: quinone reductase (NQO1), epoxide hydrolase, aflatoxin aldehyde reductase, ␥-glutamylcysteine synthase, manganese superoxide dismutase, catalase, heavy and light chains of ferritin, and leukotriene B 4 dehydrogenase [19][20][21][22].…”
Section: Role Of Enzyme Induction In Cancer Chemoprotectionmentioning
confidence: 99%